2011
DOI: 10.1063/1.3592255
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ion-acoustic structures in dusty plasma with superthermal electrons and positrons

Abstract: Nonlinear ion-acoustic structures are investigated in an unmagnetized, four-component plasma consisting of warm ions, superthermal electrons and positrons, as well as stationary charged dust impurities. The basic set of fluid equations is reduced to modified Korteweg-de Vries equation. The latter admits both solitary waves and double layers solutions. Numerical calculations indicate that these nonlinear structures cannot exist for all physical parameters. Therefore, the existence regions for both solitary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…In the electron-positron-ion-dust (EPID) plasmas, the charge of the dust grains can be either negative or positive when the number of positrons depositing on them is either smaller or larger than the number of electrons. Accordingly, it is interesting and important to study ion-acoustic waves (IAWs) in the EPID plasmas [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the electron-positron-ion-dust (EPID) plasmas, the charge of the dust grains can be either negative or positive when the number of positrons depositing on them is either smaller or larger than the number of electrons. Accordingly, it is interesting and important to study ion-acoustic waves (IAWs) in the EPID plasmas [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a positron component in conventional e-i plasma can modify the features of linear and non-linear wave structures. [22][23][24][25] Surko and Murphy [26] theoretically predicted that the annihilation of electrons and positrons is relatively unimportant over a wide range of parameters, and they also reported that, for the propagation of IAWs in e-p-i plasmas, the e-p pair annihilation can be neglected in the sense that the electron-positron lifetime is much larger than the characteristic time scale for collective oscillations. [21] The linear and non-linear propagation of IAWs in an unmagnetized e-p-i plasma have been extensively studied for the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Based on superthermal assumption, many authors have been studied the effect of superthermal particles (electrons, positrons, and ions) in different types of plasma environments. 4,8,9,[18][19][20] An electron-positron-ion (e-p-i) plasma is a fully ionized gas consisting of electrons and positrons having equal masses and charges with opposite polarity. The e-p-i plasmas are found not only in early universe 21 but also in astrophysical environments such as in magnetosphere of pulsars, 22 active galactic nuclei, 23 interstellar medium.…”
Section: Introductionmentioning
confidence: 99%